The Effect Of Teacher Professionalism On The Performance Of Christian Religious Education Teachers, Elementary Schools In Surabaya City - Sulistiani Sulis; Surja Permana (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2021)
Education is important for development in all fields in Indonesia. Whether or not the quality of education will determine the human resources produced. In the world of education, teachers play an important role, meaning that the quality of this nation's education is indirectly determined by the quality of educators or teachers. Based on the Unesco agency, Indonesia is one of the countries that has a low quality of education. The quality or low level of teacher professionalism will have an impact on low-performance results. Low teacher performance will affect the quality of students and the quality of education produced. The teacher's performance includes lesson planning, learning implementation, and learning assessment. In this study, the professionalism of teachers can be influenced by several factors, including the level of academic qualifications, certification, and teacher competence. If these three things can be fulfilled by a teacher, it is expected that the teacher has high professionalism to carry out his duties professionally so that it has an impact on better performance.